Control-oriented tools for the design and validation of the JT-60SA magnetic control system. (June 2017) - Cruz, N.; De Tommasi, G.; Mattei, M.; Mele, A.; Miyata, Y.; Pironti, A.; Suzuki, T.
Abstract: The construction and operation of the JT-60SA tokamak is the main project currently carried out jointly by Japan and the European Union under the Broader Approach agreement. Within the Integrated Project Team, Japanese and European scientists are developing and testing a number of tools to support preliminary studies and future operations of JT-60SA. Within this collaborative framework, European scientists are using a set of assessed modeling tools to design and validate possible solutions for the plasma magnetic control system of JT-60SA. This paper introduces these tools and describes a possible control architecture to be used on the JT-60SA tokamak. The effectiveness of the proposed architecture is shown by means of numerical simulations. Abstract : Graphical abstract: Abstract : Highlights: A set of control-oriented tools for magnetic control at JT-60SA has been developed. An architecture for the JT-60SA magnetic control system is proposed. A design procedure for the plasma magnetic control algorithms is given. The proposed control algorithms are validated in closed-loop simulations.